Measuring socioeconomic inequalities in postnatal health checks for newborns in Ethiopia: a decomposition analysis - Hagos, Asebe; Tiruneh, Misganaw Guadie; Abera, Kaleab Mesfin; Tsega, Yawkal; Endawkie, Abel; Negash, Wubshet Debebe; Workie, Amare Mesfin; Yohannes, Lamrot; Getnet, Mihret; Worku, Nigusu; Belay, Adina Yeshambel; Asmare, Lakew; et al. (Frontiers in Public Health, 2024)
Background: Reducing health inequity is vital for achieving the 2030 Agenda for Sustainable Development and ensuring that no one is left behind. In Ethiopia, studies have described the existence of substantial disparities in the utilization of health services across socioeconomic groups. Therefore, this study aimed to measure socioeconomic inequalities and the contributing factors in postnatal health checks for newborns in Ethiopia.We used a secondary data from the recent 2019 Ethiopia Mini Demographic and Health Survey dataset. A total weighted sample of 2105 women who gave birth in the two years preceding the survey was included in this study. The study participants were selected using multistage cluster sampling techniques. The socioeconomic inequality in postnatal health checks for newborns was measured using the Erreygers Normalized Concentration Index (ECI) and illustrated by the concentration curve. A decomposition analysis was performed to identify factors contributing to the socioeconomic related inequality in postnatal health checks for newborns in Ethiopia.The concentration curve of postnatal health checks for newborns lay below the line of equality, and the Erreygers normalized concentration index was 0.133, with a standard error = 0.0333, and a P value < 0.001; indicating that the postnatal health check for newborns was disproportionately concentrated among newborns with higher socioeconomic status. The decomposition analysis reported that ANC visit (59.22 %), household wealth index (34.43 %), and educational level of the mother (8.58 %) were the major contributors to the pro-rich socioeconomic inequalities in postnatal health checks for newborns.The finding revealed that there is a pro-rich inequality in postnatal health checks for newborns in Ethiopia. To reduce socioeconomic related health inequality, interventions should 4 target improving ANC visits, reducing the gap between the rich and poor, and increasing educational attainment among economically disadvantaged women.